Effect of Penicillium roqueforti mycotoxins on Caco-2 cells: Acute and chronic exposure. (April 2018) - Hymery, Nolwenn; Mounier, Jérome; Coton, Emmanuel
Abstract: Penicillium roqueforti is a common food and feed contaminant. However, it is also worldwide renowned for its use as a technological culture responsible for the typicity of blue-veined cheese. Members of the P. roqueforti species are also known to be able to produce secondary metabolites including mycophenolic acid (MPA) and roquefortine C (ROQ C) mycotoxins. In order to more closely simulate the reality of mycotoxin exposure through contaminated food consumption, this work investigated the toxicological effects of MPA and ROQ C not only in acute but also in chronic ( i.e. 21-days continuous exposure) conditions on Caco-2 cells. Acute exposure to high MPA or ROQ C concentrations induced an increase of IL-8 secretion. Effects of 21-days continuous exposure on barrier integrity, based on concentrations found in blue-veined cheese and mean of blue cheese intake by French consumers, were monitored. Concerning exposure to ROQ C, no alteration of the intestinal barrier was observed. In contrast, the highest tested MPA concentration (780 μM) induced a decrease in the barrier function of Caco-2 cell monolayers, but no paracellular passage of bacteria was observed. This study highlighted that exposure to MPA and ROQ C average concentrations found in blue-veined cheese does not seem to induce significant toxicological effects in the tested conditions. Highlights: Acute exposure to high MPA or ROQ C induced an increase of IL-8 secretion. Continuous exposure for 21 days to ROQ C did not lead to alteration of the intestinal barrier. Continuous exposure for 21 days to high MPA concentration induced decrease in barrier function.